PENINGKATAN TEACHER ENGAGEMENT MELALUI PENGUATAN KEPEMIMPINAN OTENTIK DAN KESEIMBANGAN KEHIDUPAN KERJA - Dian Ary Kusumah; Nandang Hidayat; Sri Setyaningsih (Universitas Pakuan, 2021)
ENHANCING TEACHER ENGAGEMENT THROUGH STRENGTHENING AUTHENTIC LEADERSHIP AND WORK-LIFE BALANCEThe purpose of this study was to determine empirically the improvement of teacher engagement through Authentic Leadership and The Work-Life Balance of Private Vocational School Teacher Foundation (GTY) in Tanah Sareal District, Bogor City. The number of research samples was 136 teachers who were taken from 206 permanent teachers from the school foundation. It was taken randomly by using proportional random sampling technique. The method was the correlation method. Hypothesis testing was using parametric statistical analysis in the form of simple and multiple linear regression analysis, simple and multiple correlation analysis as well as partial analysis at the significance level α = 0.01 and α = 0.05. This research brought three conclusions. Firstly, there was a positive and significant relationship between Authentic Leadership (X1) and Teacher Engagement (Y) which was shown by a simple linear regression equation Ŷ = 31.05 + 0.76X1 with a correlation coefficient ry1 = 0.892, the coefficient of determination Ry12 0.7050, significance a correlation of 22.89. Secondly, there was a positive and significant relationship between work-life balance (X2) and Teacher Engagement (Y) which was shown by the linear regression equation Ŷ = 28.14 + 0.78X2. with a correlation coefficient of ry2 = 0.75, the coefficient of determination ry2 2 = 0.6514 and a correlation significance of 13.21. Thirdly, there was a positive and significant relationship between authentic authentic leadership and work-life balance together with teacher engagement as indicated by the equation Ŷ = 26.05 + 0.56 X1 + 0.24 X2, the correlation coefficient ry. 12 = 0.715, the coefficient of determination ry.122 = 0.715 and the significance of the correlation was 20.43. Based on the results of the final research, it is stated that the GTY teacher engagement of private vocational schools in Tanah Sareal Sub-district-Bogor City can be strengthened by Authentic Leadership and Work-Life Balance.